2022
DOI: 10.1099/mgen.0.000849
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal MLST nucleotide identity (rMLST-NI), a rapid bacterial species identification method: application to Klebsiella and Raoultella genomic species validation

Abstract: Bacterial genomics is making an increasing contribution to the fields of medicine and public health microbiology. Consequently, accurate species identification of bacterial genomes is an important task, particularly as the number of genomes stored in online databases increases rapidly and new species are frequently discovered. Existing database entries require regular re-evaluation to ensure that species annotations are consistent with the latest species definitions. We have developed an automated method for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Results from the phylogenomic analyses agree with those of Liu et al (2020) , with species of the genus Klebsiella divided into two clades and Raoultella species constituting their own discrete clade. Furthermore, the topology of the phylogenomic tree is congruent with a previous phylogeny based on non-paralogous ribosomal MLST loci ( Bray et al, 2022 ) where the genus Raoultella is shown to separate Klebsiella into two clades, the “ pneumoniae-africana-variicola ” clade and the “ oxytoca-indica-grimontii-michiganensis ” clade.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Results from the phylogenomic analyses agree with those of Liu et al (2020) , with species of the genus Klebsiella divided into two clades and Raoultella species constituting their own discrete clade. Furthermore, the topology of the phylogenomic tree is congruent with a previous phylogeny based on non-paralogous ribosomal MLST loci ( Bray et al, 2022 ) where the genus Raoultella is shown to separate Klebsiella into two clades, the “ pneumoniae-africana-variicola ” clade and the “ oxytoca-indica-grimontii-michiganensis ” clade.…”
Section: Resultssupporting
confidence: 79%
“…The future of the genus Raoultella is currently unclear as taxonomists fail to agree on whether the genus Klebsiella is polyphyletic, or monophyletic with the inclusion of Raoultella in the Klebsiella genus clade. There is little to differentiate these two genera based on phenotype or ecology, and their phylogeny varies depending on whether it is based on core genome sequences, core protein sequences or rMLST loci ( Liu et al, 2020 ; Ma et al, 2021 ; Bray et al, 2022 ). As additional novel species are classified as belonging to either Raoultella or Klebsiella , the true taxonomy of these genera may become more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal MLST was described by Jolley et al (2012) , but this method requires gene prediction, unlike ANIm and FastANI ( Jolley et al, 2012 ). More recently, a new method for ribosomal MLST nucleotide identity (r-MLST-NI) has been developed for classifying Klebsiella and Raoultella species and may be useful for identifying other bacterial species ( Bray et al, 2022 ). Public health laboratories in the United States, including our laboratory, have transitioned to WGS analysis from conventional methods for identification and surveillance of enteric pathogens.…”
Section: Introductionmentioning
confidence: 99%